2006
DOI: 10.1063/1.2234287
|View full text |Cite
|
Sign up to set email alerts
|

Density fluctuations measured by a mm-wave collective scattering in helicon plasmas

Abstract: Density fluctuations in helicon plasmas propagating perpendicular to the static axial magnetic field are observed by using a mm-wave collective scattering method. There exist two kinds of density fluctuations, and the high-frequency fluctuation around 500kHz follows the dispersion relation of the acoustic waves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Recent experiments in helicon plasma sources have employed collective scattering diagnostics in the microwave to millimeter wavelength ranges. 1,2 Using enhanced backscattering of microwaves at the upper hybrid resonance layer, ion-acousticlike waves were observed by Altukhov et al Ion-acoustic waves were also observed with a 140 GHz millimeter-wave based scattering diagnostic by Kwak et al, similar to the system described here. Interferometers employing millimeter-wave sources have been installed on experiments ranging from a fusion class device 3 ͑DIII-D͒ to a low temperature helicon plasma.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…Recent experiments in helicon plasma sources have employed collective scattering diagnostics in the microwave to millimeter wavelength ranges. 1,2 Using enhanced backscattering of microwaves at the upper hybrid resonance layer, ion-acousticlike waves were observed by Altukhov et al Ion-acoustic waves were also observed with a 140 GHz millimeter-wave based scattering diagnostic by Kwak et al, similar to the system described here. Interferometers employing millimeter-wave sources have been installed on experiments ranging from a fusion class device 3 ͑DIII-D͒ to a low temperature helicon plasma.…”
Section: Introductionsupporting
confidence: 54%
“…Thus all optical components, except the vacuum collection mirror, fit on a 36 by 36 in. 2 the four 6 in. ports.…”
Section: Ghz Diagnostic Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser induced fluorescence (LIF) is routinely employed in helicon [16][17][18] plasma sources to measure Doppler resolved velocity distribution functions (VDF) of argon ions, argon neutrals, helium neutrals, and xenon ions. [19][20][21] The full width at half maxima of the VDF represents the average temperature of the distribution and the shift of the peak of the distribution from a standard reference line gives the ion fluid velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is possible to extract some details about the electron EDF from a Langmuir probe current versus voltage sweep, 8 the details of the ion EDF are much harder to extract from Langmuir probe measurements; neutral EDFs cannot be measured with a Langmuir probe; and any flows in the plasma make the interpretation of the electron EDF particularly problematic. 9 LIF is routinely employed in helicon [10][11][12] and other plasma sources to measure velocity distributions of argon ions, argon neutrals, helium neutrals, and xenon ions. [13][14][15] LIF is an effective and versatile technique as long as sufficiently large populations of the target species initial state are available.…”
Section: Introductionmentioning
confidence: 99%